Forex Trading and Client Management for BB Advisory - Harchandani, Pratik (ATLAS SkillTech University, 2025)
BB Advisory is one of the maximum eminent training & Consulting firm based in Bangalore, India. Our know-how mainly consciousness in stocks, forex, COMEX, INDICES & Crypto training & Consulting services. Our main focus is to facilitate people, company, Investor/traders as a torchlight to reveal the direction of trading &investment in economic marketplace. We satisfaction ourselves on being the maximum trusted consulting, putting your needs first in everything we do. BB Advisory’s curriculum and coaching approach developed student creativity, resilience and sensible skills to decorate their possibilities for better employment/ trading monetary marketplace. We provide the motivation &inspiration for college kids to be achiever, and a good way to follow found out know-how in real international surroundings through expertise the fundamental & practical components of trading
Project Report on Forex Trading and Client Management for BB Advisory (2023-2025) Under the Guidance of Prof. Vipul Pancholi
Keywords: training; Consulting; economic; marketplace; stocks; COMEX; INDICES; monetary; trading